1992
DOI: 10.1007/bf01883320
|View full text |Cite
|
Sign up to set email alerts
|

Population studies of inv(9) chromosomes in 4,300 japanese: Incidence, sex difference and clinical significance

Abstract: SummaryPopulation incidence of a chromosome 9 with an inversion of qh, inv(9), was surveyed using C-banding in a total of 4,367 Japanese which consisted of five patient groups and a normal control group. The inv(9) incidence was 1.65~ in the normal control group (n=1,513) and 1.52~ in the Down syndrome patient group (n----1,246). The incidence of female carriers was 1.7 times higher than that of male carriers in the above two groups. The sex difference was significant (p<0.05). Moreover, the incidence in the 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
25
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 24 publications
(15 reference statements)
3
25
0
Order By: Relevance
“…Among them, there were 27 cases (1.2%) of proven constitutional inv(9)(p11q13) on karyotyping of bone marrow cells. This was in keeping with the quoted incidence of pericentric inversion of chromosome 9, namely 1.0-1.7% in the Oriental population (Ko et al 1992;Yamada 1992;Teo et al 1995) and 0.9% in the Caucasian population (Tawn and Earl 1992). As pericentric inversion of chromosome 9 is not over-represented in patients with hematological malignancies, there is no evidence from our data to suggest that the presence of constitutional inv(9qh) increases the risk of hematological malignancies.…”
supporting
confidence: 57%
“…Among them, there were 27 cases (1.2%) of proven constitutional inv(9)(p11q13) on karyotyping of bone marrow cells. This was in keeping with the quoted incidence of pericentric inversion of chromosome 9, namely 1.0-1.7% in the Oriental population (Ko et al 1992;Yamada 1992;Teo et al 1995) and 0.9% in the Caucasian population (Tawn and Earl 1992). As pericentric inversion of chromosome 9 is not over-represented in patients with hematological malignancies, there is no evidence from our data to suggest that the presence of constitutional inv(9qh) increases the risk of hematological malignancies.…”
supporting
confidence: 57%
“…Unfortunately, this excess of X-bearing sperm could result from an underestimation of X chromosome nullisomy due to the absence of the X chromosome probe in this study. Nevertheless, in an epidemiological study of 4300 individuals from Japan, 25 the incidence of inv (9) carriers was about two times higher in the female group than in the male group (Po0.05).…”
Section: Discussionmentioning
confidence: 90%
“…There is a possibility that chromosomal rearrangement could interrupt the function of one or more genes close to the breakpoint. Several reports [4][5][6] suggesting that there may be a susceptibility gene for schizophrenia located at the breakpoints of inv (9), and other reports suggesting the existence of an association between inv(9) and recurrent abortions or infertility 10,11,[24][25][26] can be understood in this context.…”
Section: Discussionmentioning
confidence: 96%
“…Serra et al 8 estimated the incidence to be 0.85% among newborn infants in European populations, while Hsu et al 13 reported that the incidence differed between ethnic groups, and was lowest in Asian populations (0.26%). However, Yamada, 11 Ko et al 14 and Teo 15 analyzed the data from several Asian countries, and reported the incidence of inv (9) in the Asian population to be 1.65%, 1.20% and 1.20%, respectively. The incidences were lower in several countries, such as Taiwan and Singapore, but methodological differences might have influenced the results, as some of the studies involved were based on the analysis of newborns, while others were based on antenatal cytogenetic analysis.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation